The impact of noise exposure in Air Force Military - Mariana Correia; Teresa Matos; Helena Ribeiro; Marina Lopes; Sofia Almada (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Introduction: Military aviation is characterized by multiple noise sources, which are worrying as they exceed the legal limits required. The objective of this study is to evaluate the need to extend the monitoring program for all military exposed to aviation noise in the Air Force Units, with the specific objectives of evaluating the noise level to which they are exposed during the day and assessing the impact which it has on their quality of life.